Rancangan Sistem Pengukuran Spesific Gravity secara Real Time Berbasis Arduino Uno pada Larutan Calsium Carbonate di Claybath - Ahmad Mahfud (JURNAL CITRA WIDYA EDUKASI, 2020)
This research is a real-time measurement system design by utilizing an ultrasonic sensor that is connected to the Arduino Uno microcontroller. Testing is done by testing the performance of claybath miniature, which will separate the kernel and shell material using a suspension of calcium carbonate. Data obtained from sensor that have been previously calibrated will be analyzed, ie by comparing reference data obtained from measurement manually using a hydrometer. The result showed that the ultrasonic sensor and Arduino Uno microcontroller can be used as a specific gravity reading sensor that works in real time. The accuracy of sensor reading is 99.4% in the measurement range 1,010 - 1,120 kg/liter, with an average difference of 0.006 kg/liter.